Protocol-based management of acute pulmonary edema in pregnancy in a low-resource center - Kousalya Chakravarthy; T Swetha; Praveen K Nirmalan; Anuradha Alagandala; Nagamani Sodumu (Wolters Kluwer Medknow Publications, 2020)
Context: Acute pulmonary oedema (APO) in pregnant women is associated with increased maternal morbidity and mortality. Aim: The aim of this study was to evaluate the risk reduction strategy by a protocol-based approach to the management of APO in pregnancy in a low-resource center. Settings and Design: The study was conducted in a single obstetric tertiary care public sector hospital for 12 months. Materials and Methods: The pregnant women admitted with acute shortness of breath (SOB) were divided into two groups based on the implementation of pulmonary edema protocol. The data before protocol (Group A) and after (Group B) were compared. Results: A total of 38 patients were admitted with acute SOB. The incidence of APO was 0.10% (95% CI: 0.08,0.14). Majority (Group A: 92.87%; Group B: 81.25%) were admitted in the third trimester. Hypertension was the most common etiology (71.42% in Group A; 81.25% in Group B), followed by cardiovascular causes (42.85% in Group A; 6.25% in Group B) and sepsis (21.42% in Group A; 18.75% in Group B). Caesarean section was carried out in 57.14% in Group A; 62.5% in Group B. Noninvasive Ventilation (NIV) was started in 8 of 16 cases in Group B. Regional anesthesia was used in 87.5% in Group A and 100% in Group B. The maternal mortality was 9 (64.28%) in Group A as compared to 1 (6.25%) in Group B; P = 0.001. Conclusion: The protocol-based algorithm for APO in pregnancy decreases the maternal mortality. Hypertensive disorders of pregnancy are the most common cause followed by cardiac disease. NIV is useful in APO.